A theory of economic integration for developing countries, illustrated by Caribbean countries - Andic, Fuat M.; Andic, Suphan; Dosser, Douglas; University of Puerto Rico (Río Piedras Campus). (London : Allen and Unwin, 1971)
This study discusses the three stages of economic integration. The theory of these three stages of integration is fairly well developed for mature economies, although not entirely so.
"Prepared under the auspices of the Institute of Caribbean Studies of the University of Puerto Rico."
Includes bibliographical references.
osc 24/09/2018
Loans
Keywords: Economic integration; Caribbean Area; Developing countries